Effect of the occlusal profile on the masticatory performance of healthy dentate subjects - Giannakopoulos, Nikolaos Nikitas; Braun, Sebastian; Eberhard, Lydia; Schindler, Hans J.; Hellmann, Daniel (The international journal of prosthodontics, 2014)
Purpose: The purpose of this study was to examine, on the basis of masticatory performance (MP), total muscle work (TMW), and range of movement (RoM), whether reduction of the profile of the cusps results in loss of the biomechanical effectiveness of chewing by healthy dentate patients. Methods: Twenty healthy patients (10 female, mean age: 24.1 ± 1.2 years) chewed standardized silicone particles, performing 15 masticatory cycles. Three experimental conditions were investigated: chewing on (1) the natural dentition (ND), (2) splints with structured occlusal profiles simulating the patient's natural dentition (SS), and (3) splints with a plane surface (PS). The expectorated particles were analyzed by a validated scanning procedure. The size distribution of the particles was calculated with the Rosin-Rammler function and the mean particle sizes (X50) were determined for each experimental condition. The target variables of the experimental conditions were compared by repeated measures analysis of variance. Results: X50 values calculated for MP differed significantly (P <.002) between PS and SS, and between ND and SS. Conversely, no significant differences (P > .05) were observed between SS and ND. Regarding muscle work the EMG activity of the masseter differed significantly (P < .001) between the left and right sides, with higher values for the right (chewing) side. No significant differences (P > .05) were observed for TMW and RoM under the three test conditions. Conclusions: The results confirm the biomechanical significance of structured occlusal surfaces during chewing of brittle test food by young dentate subjects.